PENDIDIKAN HOLISTIK ISLAM DALAM PERSPEKTIF TARBIYAH, TA‘LIM, DAN TA‘DIB: ANALISIS SURAH AL-BAQARAH AYAT 151 - Fatihatus Sya'adah; Abdur Razzaq; Kristina Imron (STKIP Subang, 2025)
Holistic education in the Islamic perspective is a comprehensive approach that emphasizes the development of all human potential, including spiritual, moral, intellectual, emotional, social, and physical aspects. This study aims to explain the concept of holistic education as defined by experts and analyze the content of QS. Al-Baqarah verse 151 as the normative basis of Islamic education, and describes the integration of the concepts of tarbiyah, ta'lim, and ta'dib in forming a comprehensive education model. The research method used is a literature review tracing classical, contemporary, and Qur'anic exegesis. The results of the study show that holistic education is oriented towards the formation of a complete human being (insan kamil), in line with the educational functions brought by the Prophet Muhammad SAW in QS. Al-Baqarah 151, namely tilawah, tazkiyah, teaching the Qur'an, wisdom, and science. The integration of tarbiyah, ta'lim, and ta'dib strengthens the foundation of Islamic education, which not only transfers knowledge but also instills manners, noble character, and awareness of God. Thus, holistic Islamic education becomes an ideal model for shaping a generation with character, knowledge, and noble morals that can face global challenges without losing divine values.